2016
DOI: 10.1177/1933719115607976
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Body Mass Index and Gestational Weight Gain Have No Negative Impact on Maternal or Neonatal Iron Status

Abstract: These results suggest that adiposity-related inflammation does not override the iron-mediated signals that regulate hepcidin production during pregnancy, and in this adolescent cohort, there is no strong evidence for a detrimental effect of maternal obesity and excessive weight gain on iron status in the offspring at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 46 publications
16
88
1
Order By: Relevance
“…The high concentrations of hepcidin and ferritin measured here in cord blood are in accordance with previous observations [20][21][22][23][24][25][26][27][28][29][30]. Nevertheless, there are a handful of previous studies [21,24,31,32] involving measurements of S-hepcidin, sTfR, and S-ferritin sampled in late pregnancy as well as in cord blood. However, only two of these studies did include IL-6 [31,32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high concentrations of hepcidin and ferritin measured here in cord blood are in accordance with previous observations [20][21][22][23][24][25][26][27][28][29][30]. Nevertheless, there are a handful of previous studies [21,24,31,32] involving measurements of S-hepcidin, sTfR, and S-ferritin sampled in late pregnancy as well as in cord blood. However, only two of these studies did include IL-6 [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, there are a handful of previous studies [21,24,31,32] involving measurements of S-hepcidin, sTfR, and S-ferritin sampled in late pregnancy as well as in cord blood. However, only two of these studies did include IL-6 [31,32]. Together with these studies, the present study emphasizes the important biochemical changes in iron status as well as acute-phase reactions that occur in the transition from late pregnancy to parturition in the cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…The central finding of our study was that EPO concentration is higher in women with obesity, even when controlling for iron status and inflammation. Few other studies have explored the influence of obesity on EPO concentration; one study in adolescents [19] and another in Mexican adult women, which controlled for inflammation [20]. These studies found no differences in EPO between individuals with adequate weight or obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Some have documented that overweight women had an increased risk of low iron status and higher levels of hepcidin and maternal inflammation [17,27]. Others have shown no relation of obesity during pregnancy and iron status [28]. Furthermore, a study of two cohorts showed that higher BMI in early pregnancy was positively associated with hemoglobin and reduced risk of anemia [29].…”
Section: Discussionmentioning
confidence: 99%